2023
DOI: 10.1111/jerd.13037
|View full text |Cite
|
Sign up to set email alerts
|

Selective adhesive luting: A novel technique for improving adhesion achieved by universal resin cements

Abstract: ObjectiveWe aimed to introduce the concept of “Selective adhesive luting—SAL” which is explained through clinical steps and supported by preliminary laboratory evidence.Clinical ConsiderationsCementation with rubber dam is difficult to perform in case of short abutment teeth and/or subgingival crown margins. By means of universal resin cements/universal adhesive systems, which can be employed in self‐adhesive as well as adhesive luting procedures, this paper presents a novel technique allowing clinicians to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…One of the most important characteristics of universal resin cements is the possibility of associating these two adhesive approaches to benefit from both strategies, depending on the clinical scenario 37 . Conversely, in the re‐irradiated specimens, there were no differences between the adhesive approaches.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the most important characteristics of universal resin cements is the possibility of associating these two adhesive approaches to benefit from both strategies, depending on the clinical scenario 37 . Conversely, in the re‐irradiated specimens, there were no differences between the adhesive approaches.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the specimens irradiated with 70 Gy, the universal resin cement in the SE mode had greater bond strength than in the SA mode in all root thirds. A recent laboratory study reported that the bonding performance of universal resin cement to dentin is improved when using their specific adhesive systems 37 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations